1987
DOI: 10.1002/cne.902600404
|View full text |Cite
|
Sign up to set email alerts
|

P2, P1, and P0 myelin protein expression in developing rat sixth nerve: A quantitative immunocytochemical study

Abstract: Myelination and the expression of myelin proteins P2, P1, and P0 were studied quantitatively in the rat sixth cranial nerve during development. The postnatal development and growth of all myelin sheaths in this nerve have been studied morphometrically in a companion paper. Epon-embedded blocks with closely matched topography in the transverse plane were selected from rats perfused at ages 1-4, 8, 15, and 20 days. From each block, serial semithin sections were cut, etched, and immunostained according to the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This would correspond to the region in which we detected initial upregulation of mRNAs and suggests that transcription and translation o f myelin protein genes are closely re-lated during regeneration, as in normal development (Trapp et a]., 1987). During development, immunostainable Po is detectable before basic proteins (Hahn et al, 1987), although the convcrsc has been reported in regeneration using radiolabelled precursors with electrophoresis (Politis el al., 1982). Our results suggest that the timing of mRNAs for both Po and MBP are closely related, although the magnitudc of MBP upregulation, relative to the normal nerve, is much greater in segments undergoing myelination.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This would correspond to the region in which we detected initial upregulation of mRNAs and suggests that transcription and translation o f myelin protein genes are closely re-lated during regeneration, as in normal development (Trapp et a]., 1987). During development, immunostainable Po is detectable before basic proteins (Hahn et al, 1987), although the convcrsc has been reported in regeneration using radiolabelled precursors with electrophoresis (Politis el al., 1982). Our results suggest that the timing of mRNAs for both Po and MBP are closely related, although the magnitudc of MBP upregulation, relative to the normal nerve, is much greater in segments undergoing myelination.…”
Section: Discussionmentioning
confidence: 77%
“…The localisation of mRNAs for Po, MBP, and MAG have been fully described prcviously (Trapp et al, 1987;Webster et al: 1987;. : 1989).…”
Section: Distribution Of Myelin Protein Gene Transcripts In Myelinatimentioning
confidence: 99%
“…By performing immunostaining on cross sections of sciatic nerves, we revealed a gradual expression of Pmp2, with a higher expression in myelin sheaths associated with large axons when compared with myelin sheaths associated with smaller axons. Only very few of the smallest myelin sheaths were not stained by Pmp2, which may be a consequence of a limitation of the labeling method, as suggested earlier (Hahn et al, 1987). However the level of expression of Pmp2 seems to be strictly regulated since the amount of expression can vary substantially in adjacent Schwann cells along the same axon.…”
Section: Discussionmentioning
confidence: 82%
“…P2 mRNA has also been detected in rabbit spinal cord by Narayanan et al (1988). Recent evidence from studies on the rat sixth cranial nerve have provided evidence that, at least in this nerve, Pz is present in all the myelin sheaths in spite of previous views that P2 was absent from small myelinated fibers (Hahn et al, 1987). P2 and the MBPs are present on the cytoplasmic faces of compact myelin (Omlin et al, 1982;Trapp et al, 1984).…”
mentioning
confidence: 89%